The relative superiority of milk production of Garut sheep and its crossbred - Inounu, I; Sukmawati, S; Noor, R.R (Indonesian Journal of Animal and Veterinary Sciences, 2006)
Garut sheep (GG) is one of some native sheep that had been well known to the people of West Java. This sheep have some advantages including their ability to produce multiple birth, reach sexual maturity faster and resistant to internal parasite. However, this sheep have also some disadvantages including low milk production, high mortality and low weaning weight. Crossbreeding is one way to improve animal genetic quality. The objective of this study is to evaluate whether the Garut, St.Croix cross (HG), and Moulton Charollais cross (MG) are superior in milk production when compared to Garut sheep. This study was conducted at small ruminant experimental station of Research Institute for Animal production from June to August 2002. The superiority of the crossed sheep was determined by subtracting the average milk production of the crossed sheep (HG or MG) and Garut sheep and then divided the values by the average milk production of Garut sheep, except for the threeway crosses (MHG and HMG) is calculated from the difference in milk production between the means of threeway crossbred with the means of two parents (MG and HG). The data had been corrected by parity and type of birth. The General Linear model of SAS was used to calculate the least square means. Average milk production from GG, MG, HG, MHG and HMG ewes in this study were respectivelly 53.41, 59.48, 55.89, 44.87 and 54.66 kg. The relative superiority for milk production of MG and HG were 11% and 5% over Garut sheep respectively and for the threeway crossbred MHG/HMG was -14% over their parents (MG and HG). Key Words: Milk Production, St.Croix, Moulton Charollais, Garut, Crossing